Learners’ Language Learning Style Preferences, Class Level, Gender, and Using Mobile Apps for EFL Learning Among Tunisian University Students (Journal of Foreign Language Teaching and Learning, 2023)
Currently, the utilization of mobile devices and more specifically mobile language applications is a current ongoing tendency. In line with this trend, this study investigated the linkage between language learning style preferences, class level, and gender on the one hand and the use of mobile applications for EFL learning among university students in Tunisia on the other hand. The considered variables were gauged using a Likert-scale response format questionnaire. The subjects were 180 Tunisian university students at the Higher Institute of Management of Gabes aged 19 to 28. Two data analysis procedures were used: namely, the Spearman Rho correlation giving insight into the correlations among the study variables, and the alpha internal consistency coefficient informing about the reliability of its instrument. Based on the study findings, students’ language learning style preferences proved to have a direct bearing on the use of mobile applications for EFL learning. Concerning the link between class level and mobile applications for EFL learning use, no meaningful relationships were registered between these two variables. As regards the correlation between gender and the use of mobile applications for EFL learning, no significant difference was detected between male students and their female counterparts. Through the achieved results, it is recommended that the interrelationship between students' differences and the use of mobile applications for EFL learning is a field of research that merits further scientific exploration to shed more light on the existing literature regarding the use of mobile applications for EFL learning.